2012
DOI: 10.1007/s10059-012-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Accessory Molecule Trim59 Involved in Cytotoxicity of BCG-Activated Macrophages

Abstract: BCG-activated macrophages (BAM) could kill the tumor cells through cell-cell contact. In this process membrane proteins play an important role. However, up to date, few membrane proteins were revealed. In this study, we selected a surface molecule named Trim59, which was specifically expressed on BAM membrane (compared with the negative control). We cloned and prokaryoticly expressed the extracellular domain of Trim59, purified the recombinant protein and generated polyclonal antibodies. Immunohistochemistry s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…TRIM59 can also regulate autophagy by modulating both the transcription and ubiquitination of BECN1 [42]. Interestingly, we found that TRIM59 expression is induced in BCG-stimulated macrophages and mediates a cytotoxic effect by direct cell contact on MCA207 fibrosarcoma cells [20]. In the present work, TRIM59 deficiency stimulated the metastatic potential of melanoma cells, suggesting that expression of TRIM59 in macrophages may have antitumor effects.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…TRIM59 can also regulate autophagy by modulating both the transcription and ubiquitination of BECN1 [42]. Interestingly, we found that TRIM59 expression is induced in BCG-stimulated macrophages and mediates a cytotoxic effect by direct cell contact on MCA207 fibrosarcoma cells [20]. In the present work, TRIM59 deficiency stimulated the metastatic potential of melanoma cells, suggesting that expression of TRIM59 in macrophages may have antitumor effects.…”
Section: Discussionmentioning
confidence: 49%
“…Our previous work showed that TRIM59 may be an essential molecule underlying the cytotoxic effect of bacillus Calmette Guérin (BCG) -activated macrophages on MCA207 fibrosarcoma cells [20]. In preliminary experiments, we also observed that the supernatant of RAW264.7 cells overexpressing TRIM59 had a strong cytotoxic effect on mouse B16 melanoma cell lines, and this effect was attenuated by a TRIM59-blockingantibody (data not shown).…”
Section: Introductionmentioning
confidence: 89%
“…Trim59, a member of the tripartite motif (TRIM)-containing protein superfamily, is characterized by one or two zinc binding motifs, an associated coiled-coil region and a RING-finger domain 10 . Previous studies show that Trim59 participates in many pathological regulation such as inflammation 11 , cytotoxicity 12 , and especially tumorigenesis 13 . Here we found that Trim59 plays a vital role in mouse early embryonic development stage.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, we proved that TRIM59 in myeloid derived macrophages protected mice from sepsis by regulating inflammation and phagocytosis. Our previous study found that TRIM59 promoted phagocytosis activity in the RAW264.7 cell line (21). Phagocytosis plays an important role in bacteria invasion, so we hypothesized that TRIM59 could affect sepsis by regulating macrophage phagocytosis.…”
Section: Discussionmentioning
confidence: 94%